ANALISIS MINAT BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI SDN 3 DUNGUSWIRU - Nisa, Uswatun; Sapitri, Intan; Koswara Adiredja, Rajji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the learning interest of fifth-grade students in mathematics learning at SDN 3 Dunguswiru. This research uses a quantitative descriptive approach with a purposive sampling technique. The subjects of this study were 29 fifth-grade students. Data were collected through a questionnaire instrument consisting of 19 valid items after validity and reliability testing using SPSS, with a Cronbach Alpha value of 0.884 (very high reliability). The data analysis technique used was descriptive statistics with percentages. The results showed that 79% of students (23 students) were in the high interest category, 21% (6 students) were in the moderate interest category, and no students were in the low interest category. However, a finding also emerged that 79% of students experienced high levels of anxiety in mathematics learning. These findings indicate that although students generally show high enthusiasm and interest in mathematics, high anxiety levels still need to be addressed through varied, supportive, and student-centered learning strategies. Keywords: learning interest, mathematics, elementary school, descriptive quantitative